An Econometric Approach on Shadow economy in European countries - PETRIC Nicolae (Annals of the University of Oradea: Economic Science, 2019)
The present article investigates the relationship between shadow economy as a percentage of GDP, direct and indirect taxes, taxes centralized by the government, personal and corporate income taxes, value added taxes. The country sample encompasses EU-28 member states, alongside Iceland and Norway, while the period analyzed spans from 2004 until 2016. By means of four econometric models that took into consideration linear and nonlinear effects, analyses indicated that there was a strong relationship between shadow economy and fiscal pressure across all countries.